2014
DOI: 10.1021/bi5000756
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Antigen Mutation Increases the pH Threshold of Anthrax Toxin Receptor 2-Mediated Pore Formation

Abstract: Anthrax toxin protective antigen (PA) binds cellular receptors and self-assembles into oligomeric prepores. A prepore converts to a protein translocating pore after it has been transported to an endosome where the low pH triggers formation of a membrane-spanning β-barrel channel. Formation of this channel occurs after some PA–receptor contacts are broken to allow pore formation, while others are retained to preserve receptor association. The interaction between PA and anthrax toxin receptor 1 (ANTXR1) is weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the residue G342 of PA was found to be involved in receptor-specific binding and pore formation. Replacement of G342 with a hydrophobic residue, such as valine, leucine, isoleucine or tryptophan, increased the binding of PA to ANTXR1-expressing cells and decreased the binding of PA to ANTXR2-expressing cells [ 43 ].…”
Section: The Vwa Domain Of Antxr2mentioning
confidence: 99%
“…Moreover, the residue G342 of PA was found to be involved in receptor-specific binding and pore formation. Replacement of G342 with a hydrophobic residue, such as valine, leucine, isoleucine or tryptophan, increased the binding of PA to ANTXR1-expressing cells and decreased the binding of PA to ANTXR2-expressing cells [ 43 ].…”
Section: The Vwa Domain Of Antxr2mentioning
confidence: 99%
“…Most recently, a study has shown that binding of the VWA domain largely increases the stability of PA and the effect reaches up to 70 Å from the receptor binding interface [ 20 ]. While the role of VWA domain in receptor-PA interaction and in PA pore formation has been well studied [ 21 25 ], little is known about the structure and function of the stalk region (219–318). Recently, we have found that the stalk region is an immunoglobulin-like (Ig) domain and the disulfide bonds in this domain are essential for functioning of the PA pore [ 26 ].…”
Section: Introductionmentioning
confidence: 99%